Demonstration of Physicochemical and Functional Similarity of Biosimilar Adalimumab-aqvh to Adalimumab - Yijia Jiang; Taruna Arora; Scott Klakamp; Janice Davis; Yasmin A. Chandrasekher; Glen Young; Yue Du; Bin Yu; Karen J. Miller (Adis, Springer Healthcare, 2023)
Abstract Background Adalimumab-aqvh/CHS-1420 (YUSIMRYTM) (hereafter referred to as adalimumab-aqvh) was recently approved by the US Food and Drug Administration as a biosimilar for adalimumab. Objective The current study was conducted to investigate the analytical similarity of adalimumab-aqvh and the reference product, adalimumab. Methods The structural, functional, and stability attributes of adalimumab-aqvh and adalimumab were compared using state-of-the-art assays. The primary structure, disulfide structure, glycan profile, secondary and tertiary structures, molar mass, size variants, free thiol, charge variants, hydrophobic variants, post-translational modifications, subvisible particles, host cell proteins, and protein concentration were investigated. The functional similarity between adalimumab-aqvh and adalimumab was demonstrated by comparing fragment antigen-binding (Fab)-associated and fragment crystallizable (Fc)-associated biological activities. The stability of adalimumab-aqvh and of adalimumab was compared through forced degradation. Results The structural attributes of adalimumab-aqvh were identical to those of adalimumab or met the similarity criteria, with a few exceptions. Adalimumab-aqvh and adalimumab exhibited comparable stability profiles and functional activities. Any observed differences in the physiochemical attributes did not impact the conclusion of similarity because they did not influence any functional activities related to the adalimumab mechanism of action. Conclusion The structural, functional, and stability data provide convincing evidence of biosimilarity between adalimumab-aqvh and the reference product, adalimumab.